Pengaruh Disiplin Kerja dan Motivasi Kerja Terhadap Kinerja Karyawan Pada Kantor Kementerian Desa dan Pembangunan Daerah Tertinggal - Hasanah, Maulida; Aprillia , Frida; Siboro, Sonny Fransisco (CV Warnak Johanna Nusantara, 2026)
In the era of globalization, organizations are required to maintain optimal employee performance to remain competitive. However, problems persist, such as low discipline in the form of late attendance and untimely work, as well as low motivation due to a lack of training and recognition. This study aims to analyze the influence of work discipline and work motivation on employee performance at the Ministry of Villages and Development of Disadvantaged Regions.The study used quantitative methods, with a population of 92 employees in the Bureau of Organization, Human Resources, and Bureaucratic Reform, and a sample of 48 respondents. Data were collected through observation and questionnaires and analyzed using multiple linear regression with SPSS version 27. The results show that work discipline significantly influences employee performance, with a calculated t-value of 5.162 > t-table 2.014 and a significance level of 0.000 < 0.05. Work motivation also significantly influences employee performance, with a calculated t-value of 3.773 > t-table 2.014 and a significance level of 0.000 < 0.05. Simultaneously, work discipline and work motivation significantly influence employee performance, with a calculated f value of 16.911 > f table 2.42 and a significance level of 0.000 < 0.05. The coefficient of determination indicates that work discipline and work motivation simultaneously influence employee performance by 42.9%, while other factors outside this study influence the remaining 57.1%. Thus, work discipline and work motivation have a positive and significant influence on employee performance.